THE INFLUENCE OF PRINCIPAL'S VISIONARY LEADERSHIP, ORGANIZATIONAL CULTURE AND WORK MOTIVATION ON JUNIOR HIGH SCHOOL TEACHERS' JOB COMMITMENT - Ismawan, Indra; Marwan, Marwan; Gani, Muzakkar A. (Jurnal As-Salam, 2025)
This study examines the impact of independent and dependent variables on Junior High Schools in Sub Rayon 05, North Aceh Regency. The benefits of this study are to be a reference material and increase knowledge in the field of visionary leadership of school principals, organizational culture, task commitment and work motivation and to provide information for junior high school principals in Sub Rayon 05 in particular and junior high school principals in North Aceh Regency in general. This study applies a quantitative approach, with data collection techniques in this study with interviews, questionnaires, and documentation. The research subjects consisted of 142 teachers. The results of the display of the principal's visionary leadership variable significantly affect task commitment. From the organizational culture side, it significantly affects commitment. At the same time, the principal's visionary leadership side also significantly affects work motivation, and organizational culture affects work motivation. From the work motivation side, it significantly affects the task commitment of junior high school teachers in Sub Rayon 05, North Aceh Regency. In addition, the principal's visionary leadership, organizational culture and work motivation simultaneously affect the task commitment of junior high school teachers in Sub Rayon 05, North Aceh Regency.